Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Produktivitas Kerja Karyawan pada PT Mensa Binasukses - Deby Irama (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of work discipline and work motivation on employee productivity at PT Mensa Binasukses. The method used is quantitative with a descriptive approach and multiple linear regression analysis. The research sample consists of 60 employees, selected using a saturated sampling technique. Data were collected through questionnaires that assess various aspects of work discipline, work motivation, and employee productivity. The collected data were then analyzed using SPSS version 25 to determine the relationship between the independent variables (work discipline and work motivation) and the dependent variable (employee productivity). The results of this study indicate that both work discipline and work motivation have a positive and significant effect on employee productivity. This was demonstrated through both partial and simultaneous analysis, where work discipline and motivation individually and collectively influenced productivity outcomes. These findings suggest that improvements in work discipline and motivation can lead to increased productivity among employees. The company is advised to continuously implement strategies aimed at enhancing these two factors, such as through regular training programs, providing incentives, and fostering a supportive work environment. These efforts will contribute to more optimal productivity and greater organizational success. The study concludes that attention to employee work discipline and motivation is essential for maintaining a high level of productivity in the workplace.